Integrated Knowledge Translation in Non-Communicable Disease Research in Sub-Saharan Africa: A Comparison of Systematic and Ad Hoc Stakeholder Engagement - Mpando, Talitha L.; Sell, Kerstin; Delobelle, Peter; Osuret, Jimmy; Niyibizi, Jean Berchmans; Ntawuyirushintege, Seleman; Geremew, Bezinash; Jessani, Nasreen S. (Frontiers in Tropical Diseases, 2021)
Background Low- and middle-income countries (LMICs) are currently experiencing an increasing prevalence of non-communicable diseases (NCDs). To address this as well as other health challenges, Integrated Knowledge Translation (IKT) approaches to build mutually beneficial relationships between researchers and decision-makers can concurrently inform research as well as enhance evidence use in policy and practice. The Collaboration for Evidence-Based Healthcare and Public Health in Africa (CEBHA+) is a research consortium which conducts research on NCDs and uses an IKT approach to facilitate the uptake of this research in five African countries: Ethiopia, Uganda, Rwanda, Malawi, and South Africa. Tailored IKT strategies were designed and implemented to plan and guide stakeholder engagement. This systematic approach contrasts with more commonly used ad hoc approaches to stakeholder engagement. Methods In this article, we explore the experiences of researchers engaged in the CEBHA+ IKT approach across the five African countries. Data sources included: 1) an informal document review of CEBHA+ country-specific IKT strategies, IKT team meeting minutes and activity reports, and 2) a semi-structured survey of IKT implementers to elicit country-specific experiences on actual implementation and adaptation of the IKT strategies. Results were collated and contrasted across all CEBHA+ countries with a focus on systematic versus ad hoc approaches to engagement. Results South Africa, Malawi and Ethiopia country teams indicated that their engagements benefited from a systematic IKT strategy. This was especially the case in the early stages of the project as it allowed focused and intentional engagement. However, ad hoc engagement was still required as new professional relationships developed, and contextual circumstances - including the SARS-CoV-2 pandemic - required responsive engagement with decision-makers and other stakeholders. In Rwanda and Uganda, continuous systematic engagement was found to bolster ownership of the research at both community and national levels. Conclusion Political and health climates are constantly shifting with a need to maintain flexibility in how IKT strategies are implemented. While strategic IKT can benefit from deliberate planning and stakeholder engagement, there is value in remaining flexible to respond to the needs of stakeholders and contextual circumstances. This paper highlights how IKT implementers in the five African CEBHA+ countries responded to this challenge.